DENSITY AND DIVERSITY OF BIRDS IN THE AGRICULTURAL LANDSCAPE OF POTHWAR PLATEAU, PAKISTAN - M. Sarwar (Journal of Animal and Plant Sciences, 2019)
Due its unique topography and climatic conditions Pothwar plateau of Pakistan is famous for hosting important floral and faunal diversity of Pakistan but no report is available on the current status and population dynamics of bird species in this area. In this study the number and species richness of birds associated with different agricultural landscapes on the plateau were estimated. The study was conducted in 4 selected study sites (10 x 10 ha each) based on monthly visual surveys over 2 years. Two of the sites were drier where wheat and groundnut were the main crops whereas the other two sites were located close to rain water ponds where wheat, maize and millet were cultivated. A total of 29 bird species were recorded, of which 24 were residents while the remaining 5 were winter visitors. Both bird density and species richness decreased during summer (May-July) at all sites across the 2 years. Comparing sampling sites on the basis of cropping system and water availability showed that more bird species, especially the over-wintering species, were found at sites close to water resources. Thus the higher number of species in areas with a wheat-maize/millet cropping system was probably due to water availability.
Keywords: Bird density; Bird diversity; Birds in croplands; Species richness